The Meaning of the Turkish Maritime for Atatürk and Its Reflections in The Early Republican Period - Funda Songur (Yakın Dönem Türkiye Araştırmaları)
The necessity to have the political, military, and economic power to protect its national rights and interests at sea has been one of the critical issues since the establishment of the Turkish state. In Atatürk’s words, the Turks did not accomplish significant naval operations in the era of the modern navy, and this situation revealed the need for a strong Turkish navy. Given that strengthening only the naval force would not be enough, steps were taken to develop theTurkish maritime political, economic, and cultural aspects. In this article, the Turkish maritime in the Early Republican Period is discussed in the light of periodicals, maritime reports, archive documents, and secondary sources. As a result of this study, which aims to evaluate maritime in detail with political, naval, economic, and cultural efforts, the importance attributed to the Turkish maritime under the leadership of Atatürk is examined, and its transformation into a national maritime power is revealed.